Leading Adaptive Teams in Healthcare Organizations. - O'Brien, Kurt C. (Business Expert Press, 2017)
The objective of Leading Adaptive Teams in Healthcare Organizations is to provide specific frameworks, models, and skills that can guide healthcare leaders as they engage their teams in navigating an increasingly complex and uncertain environment. The emphasis here is squarely on teams and the leader's role in leveraging collaborative group process to drive better patient outcomes. Because of the high level of complexity today's healthcare organizations operate in, new frameworks and models are needed; this book is an attempt to contribute to this ongoing dialogue and body of knowledge.